Angiosome-Guided Perfusion Decellularization of Fasciocutaneous Flaps - Yang, Liya; Bai, Xueshan; Liu, Yuanbo; Zhu, Shan; Li, Shanshan; Chen, Zixiang; Han, Tinglu; Jin, Shengyang; Zang, Mengqing (Journal of Reconstructive Microsurgery, 2024)
Background Tissue engineering based on whole-organ perfusion decellularization has successfully generated small-animal organs, including the heart and limbs. Herein, we aimed to use angiosome-guided perfusion decellularization to develop an acellular fasciocutaneous flap matrix with an intact vascular network.Methods Abdominal flaps of rats were harvested, and the vascular pedicle (iliac artery and vein) was dissected and injected with methylene blue to identify the angiosome region and determine the flap dimension for harvesting. To decellularize flaps, the iliac artery was perfused sequentially with 1% sodium dodecyl sulfate (SDS), deionized water, and 1% Triton-X100. Gross morphology, histology, and DNA quantity of flaps were then obtained. Flaps were also subjected to glycosaminoglycan (GAG) and hydroxyproline content assays and computed tomography angiography.Results Histological assessment indicated that cellular content was completely removed in all flap layers following a 10-hour perfusion in SDS. DNA quantification confirmed 81% DNA removal. Based on biochemical assays, decellularized flaps had hydroxyproline content comparable with that of native flaps, although significantly fewer GAGs (p = 0.0019). Histology and computed tomography angiography illustrated the integrity and perfusability of the vascular system.Conclusion The proposed angiosome-guided perfusion decellularization protocol could effectively remove cellular content from rat fasciocutaneous flaps and preserve the integrity of innate vascular networks.
Keywords: angiosome; perfusion decellularization; flap substitute; extracellular matrix scaffold; whole-organ engineering